PERBEDAAN ACTUAL RETURN, ABNORMAL RETURN, TRADING VOLUME ACTIVITY DAN SECURITY RETURN VARIABILITY SAHAM SEBELUM DAN SETELAH MERGER - Nurussobakh Nurussobakh (University of Merdeka Malang, 2009)
A research was needed for knowing how far merger could build positive impact tothe development of a company. By compiling this research, we tried to know the average ofactual return, abnormal return, trading volume activity (TVA) and security return variability(SRV) of share before and after merger in 2006 at the companies listed in BEI. This researchused purposive sampling in defining the samples of research. The period of research was 50days divided into 25 days before merger and 25 days after merger. Besides, the examinationwas done continuously for 40 days, 30 days, 20 days, and 10 days in the period of research toknow how fast merger showed the significant difference to the four variables examined. Theresearch showed that the average of actual return and abnormal return of share of the companieshad gone higher or relative low before and after merger. On the other hand, the average ofTVA had gone higher or relative high and the average of SRV had gone lower down or relativehigh. The statistic showed that there was no significant difference happened to actual return,abnormal return and SRV of share of companies before and after merger. On other hand, TVAof share showed a significant difference based on asymptotic significant.